2020
DOI: 10.1371/journal.pone.0236780
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole-body electromyostimulation (WB-EMS) in comparison to a multimodal treatment concept in patients with non-specific chronic back pain—A prospective clinical intervention study

Abstract: Background According to present guidelines, active exercise is one key component in the comprehensive treatment of nonspecific chronic back pain (NSCBP). Whole body electromyostimulation (WB-EMS) is a safe, and time-effective training method, that may be effective in NSCBP-patients. Methods In this prospective and controlled nonrandomized clinical study, two therapeutic approaches were compared. One group received 20 minutes WB-EMS per week. An active control group (ACG) received a multimodal therapy program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 62 publications
0
24
0
16
Order By: Relevance
“…In the field of WB-EMS, there are only one meta-analysis of individual patient data ( Kemmler et al, 2017 ) and one controlled non-randomized clinical intervention study ( Konrad et al, 2020 ) focusing on low back pain. The included studies of the meta-analysis show a wide range of training duration from 14 weeks to 12 months with different training volume and frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of WB-EMS, there are only one meta-analysis of individual patient data ( Kemmler et al, 2017 ) and one controlled non-randomized clinical intervention study ( Konrad et al, 2020 ) focusing on low back pain. The included studies of the meta-analysis show a wide range of training duration from 14 weeks to 12 months with different training volume and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the clinical intervention study confirm our findings. A WB-EMS training program, conducted over 24 weeks with a comparable training volume (1x/week, 20 min) showed significant and clinically important pain reductions by 2 points on the NRS 0–10 scale ( Konrad et al, 2020 ). The slightly greater pain reductions can be explained by the longer training period (12 vs. 24 weeks) and the higher basal pain values.…”
Section: Discussionmentioning
confidence: 99%
“…It might be surprising, but in contrast to corresponding commercial advertising, the evidence for a positive effect of once-weekly 20-min sessions of WB-EMS is very limited in healthy adults. To the best of our knowledge [ 11 ], only three studies address this issue in people with chronic unspecific low-back pain [ 15 , 27 ] or sarcopenic obesity [ 33 ]; however, the two studies that focus on this issue show inconsistent results on strength and body composition parameters. In summary, we observed positive effects on MITS and MILES that still remained significant after adjusting for multiple testing of the (two) primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding and the limited statistical power to address this outcome might put the (only) non-significant reductions of pain frequency ( p = 0.078) and intensity ( p = 0.152) into a better perspective. However, reviewing the high evidence on WB-EMS effects on low-back pain provided by recent specific studies [ 15 , 39 , 40 ], this issue might be one of the most clearly confirmed outcomes in WB-EMS research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation